Entre a metaxis e a filosofia da práxis : teatro do oprimido-perspectivas para o teatro na educação - Moraes, Michele Adriana de (2015)
The present study is linked to the Postgraduate Program in Education of UFSCar, under the research line Theories and Practice in School Education. The central theme of this study is the Theatre and Education. The object of the study has as references Theatre of the Oppressed’s working techniques, a theatrical teaching methodology created by Augusto Boal, who seeks to identify the injustices established in oppressed-oppressor’s relations and overcome them through Concrete and Continued Social Actions. Since it is a Library imprint of research, we look for material at dissertation’s bank and Capes’s Theses, who fieldworks were conducted in formal and non-formal learning environments who practices the Theater of the Oppressed methodology. We investigated these theses and dissertations understand the interpretation and the use they make of the Oppressed Theatre. We grouped the works in two (02) themes; School Education (representing formal learning environments) and Social Education Processes (representing informal learning environments). For the development of this research we used the content analysis technique, beyond the presentation of quantitative and qualitative data of theses and dissertations.